Tobin's Q as a measure of airline performance. - Poh, Kok Hong. (2008)
This is a performance study of the global airlines industry using Tobin's q. We attempt to establish both theoretically and empirically that q is a superior financial performance measure over other commonly used financial ratios. We also find a significant relationship between q and operational profitability and yield.